Students’ perceptions on diagnosis and treatment of occlusal surface of first molars - Beatriz Vieira de Paiva; Fernanda Ladico Miura; Silvana de Andrade Silvestre de Lima; Danielly Cunha Araújo Ferreira; Alessandra Maia de Castro; Fabiana Sodré de Oliveira (Revista Sul-Brasileira de Odontologia, 2015)
Accurate diagnosis of dental caries is a fundamental requirement in health care. Objective: The aim of this study was to evaluate the opinions of undergraduates concerning different conditions of the occlusal surface of permanent first molar. Material and methods: Two experienced and trained examiners, using visual and radiographic examinations, classified five occlusal surfaces of permanent first molars. The surfaces were photographed and presented to students with a questionnaire about classification of occlusal surfaces, methods used to aid caries diagnosis and type of treatment to be applied. The answers were classified as correct and incorrect and submitted to Chi-square test (p < 0.05). Results: The results showed a higher percentage of correct answers regarding to dentine caries (87.95%) and no caries (84.34%). For all surface conditions, the methods most commonly used to aid diagnose were professional prophylaxis, good lighting, drying and dental probe. Considering the treatment, a greater number of correct answers were obtained for the surface with dentine caries, with indication of conventional (65.06%) and/or preventive restoration (33.73%) and no caries without treatment need or sealant (53.01%). For students at 6th, 7th and 8th semesters, the percentage of correct answers for classification and treatment was 72.31%, 58.33% and 62.94%, respectively, without statistically significant differences (p < 0.05). Conclusion: It was concluded that the opinion of students differed regarding to the diagnosis and treatment mainly when the occlusal surface showed early stages of dental caries.